Iberorhyzobius Raimundo & Canepari gen. nov., for Coccidula rondensis Eizaguirre (Coleoptera: Coccinellidae) - Raimundo, Armando; Canepari, Claudio; Mendel, Zvi; Branco, Manuela; Franco, José Carlos (Zootaxa, 2006)
A new genus of Coccidulinae from the Iberian Peninsula, Iberorhyzobius Raimundo & Canepari, is described for the species Coccidula rondensis Eizaguirre, 2004. Description and illustrations of the adult and larva are presented. Differences between Iberorhyzobius and other European Coccidulini are discussed. Adults and larvae of this species were collected in maritime pine stands, Pinus pinaster Aiton. Larvae were found preying upon ovisacs of the pine bast scale Matsucoccus feytaudi Ducasse. Both adults and larvae were lured by the sex pheromone of this prey. Our findings support the hypothesis that the new genus is endemic to the Iberian Peninsula.